Community-Based Planning For the Improvement of Housing and Settlements Urban Slum Areas in Karet-Kuningan Sub-District, South Jakarta, Indonesia - Dinar Oktaria Supardi Kusumah (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
One of the fundamental human necessities is housing and settlements, which also play a significant role in raising people's standard of living and dignity in a fair and prosperous society. Another aspect of national development that must be consistently enhanced and developed in a coordinated, planned, sustainable, and integrated way is housing and settlements. The quality of the environment or what are later referred to as "Slum Areas" will tend to deteriorate if housing and settlement development is less coordinated, planned, integrated, and pays less attention to the completeness of basic infrastructure and facilities like clean water, sanitation, waste management systems, and rainwater drainage. This study's focus is on residential neighborhoods that are set up according to land use, which includes the actual Through information on current environmental conditions, environmental potential, environmental issues, work programs, and residential area planning papers involving the role of active community members and stakeholders, the community's social, cultural, and economic components are examined. A qualitative descriptive approach is employed, for Examine slum management policies, programs, and studies, including spatial planning, and create profiles of slum areas at the arrangement's location. Community help to find issues and opportunities based on the findings of mapping the state of residential areas from three (three) perspectives: the physical environment, the sociocultural context, and the community's economics. Create ideas and plans for dealing with settlement planning.